GE_GERICHTE P/19548/2017 vom 13. März 2024 - GE Cour de justice (2024)
MENACE(DROIT PÉNAL);LÉSION CORPORELLE SIMPLE;CONTRAINTE(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);MEURTRE;PRINCIPE DE LA CÉLÉRITÉ;EXPULSION(DROIT DES ÉTRANGERS) | CP.180; CP.123; CP.22; CP.181; CP.111; CP.16; CP.66abis; CP.51